Altered processing of communication signals in the subcortical auditory sensory pathway in autism. Issue 6 (17th January 2022) - Schelinski, Stefanie; Tabas, Alejandro; von Kriegstein, Katharina
Abstract: Autism spectrum disorder (ASD) is characterised by social communication difficulties. These difficulties have been mainly explained by cognitive, motivational, and emotional alterations in ASD. The communication difficulties could, however, also be associated with altered sensory processing of communication signals. Here, we assessed the functional integrity of auditory sensory pathway nuclei in ASD in three independent functional magnetic resonance imaging experiments. We focused on two aspects of auditory communication that are impaired in ASD: voice identity perception, and recognising speech‐in‐noise. We found reduced processing in adults with ASD as compared to typically developed control groups (pairwise matched on sex, age, and full‐scale IQ) in the central midbrain structure of the auditory pathway (inferior colliculus [IC]). The right IC responded less in the ASD as compared to the control group for voice identity, in contrast to speech recognition. The right IC also responded less in the ASD as compared to the control group when passively listening to vocal in contrast to non‐vocal sounds. Within the control group, the left and right IC responded more when recognising speech‐in‐noise as compared to when recognising speech without additional noise. In the ASD group, this was only the case in the left, but not the right IC. The results show that communication signal processing in ASD is associated with reduced subcortical sensory functioning in the midbrain. The results highlight the importance of considering sensory processing alterations in explaining communication difficulties, which are at the core of ASD. Abstract : Voice processing is an evolutionary preserved process and voice‐specific brain responses develop early in human life. Impaired voice processing is a characteristic behavioural symptom in autism, a neurodevelopmental condition associated with impaired social communication. Here, we show, in three neuroimaging experiments, that adults with autism have reduced voice processing in the central midbrain structure of the subcortical auditory pathway. The results show that communication signal processing in autism is associated with reduced subcortical sensory functioning in the midbrain, highlighting the importance of considering sensory processing alterations in explaining communication difficulties.